2018
DOI: 10.1051/matecconf/201819505008
|View full text |Cite
|
Sign up to set email alerts
|

The analysis of Ancol polder system as flood prevention infrastructure in Jakarta

Abstract: Abstract. Flooding in Jakarta is a common phenomenon that is caused by climate changes. One of the government's actions is building polders in Jakarta to prevent the flooding. However, these polders seem to not significantly affect it. This research aims to analyse Ancol Polder in North Jakarta as flood prevention infrastructure. This research uses Muskingum Cunge and O'Donnel and Muskingum Extended methods to analyse the hydrographs. This research analyses the performance of channel capacity by HEC-RAS modell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…The results showed that constructing polders would increase economic losses in extreme climates (Bouwer et al, 2010). Mantasa Salve Prastica (2018) conducted a study on the Ancol polder in northern Jakarta to investigate the polder's effect on the river's capacity and stability by developing a HEC‐RAS model and exploring whether the polder can be used as a flood control infrastructure (Mantasa Salve Prastica, 2018). Laks and Walczak (2020) proposed that polder construction should be carried out using modern solutions, such as GIS (Geographic Information System, a system that creates, manages, analyzes, and maps all types of data) tools and multicriteria decision analysis methods for flood hazard mapping and flood risk assessment (Laks & Walczak, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that constructing polders would increase economic losses in extreme climates (Bouwer et al, 2010). Mantasa Salve Prastica (2018) conducted a study on the Ancol polder in northern Jakarta to investigate the polder's effect on the river's capacity and stability by developing a HEC‐RAS model and exploring whether the polder can be used as a flood control infrastructure (Mantasa Salve Prastica, 2018). Laks and Walczak (2020) proposed that polder construction should be carried out using modern solutions, such as GIS (Geographic Information System, a system that creates, manages, analyzes, and maps all types of data) tools and multicriteria decision analysis methods for flood hazard mapping and flood risk assessment (Laks & Walczak, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The existence of this problem makes Polder the solution (Baan and Klijin 2004;Hoes and Van De Giesen 2015). In its implementation the polder system has been applied in various locations in Indonesia in dealing Proceedings of the 3 rd Asia Pacific International Conference on Industrial Engineering and Operations Management, Johor Bahru, Malaysia, September 13-15, 2022 © IEOM Society International with flood problems such as in the Muara Angke area, Jakarta (Sari et al 2019), Semarang (Pratiwi and Wahyu 2021), Ancol, Jakarta (Prastica 2018).…”
Section: Introductionmentioning
confidence: 99%